Metalinės diržų ir kamanų detalės iš Stragnų kapinyno. Romėniškojo laikotarpio dirbiniai rinkinyje be lauko metrikų - Banytė-Rowell, Rasa (Archaeologia Lituana, 2004)
This article represents an analyse of part of the finds from Stragnai cemetery (Klaipėda district, West Lithuania), particularly the remains of grave goods which we can recognise as metal ornaments or functional details of belts and bridles from Roman Iron age and some Early Migration period graves. These items are the result of amateur excavations in period between 1896–1901 or probably also in 1911 by the Šilutė (formely Heydekrug) estate owner Hugo Scheu, and his son Eric Scheu. At that time the Klaipėda district (formerly Memelland) was part of Eastern Prussia and here the history of archeological investigations of the end of 19th cent.-beginning of the 20th cent. were closely related to the enthusiastic activity of local collectors of antiquities and their connections with national Prussian antiquities societies. Hugo Scheu was a number of Prusian Antiquities Society in Königsberg (Altertumsgesellschaft Prussia zu Königsberg) and mostly his activities and personal assistence caused the appearance of such contemporary professionals as professor Adalbert Bezzenberger from Königsberg in Memeland archeological field investigations. The first group of loose finds selected in the fields between the villages of Stragnai and Skėriai (Skören) reached the Prussia Museum in Königsberg in 1889 as donations from local landowners. From 1896 the latter somehow gave permission for Scheu to look for items in Stragnai/Skėriai fields or even to make amateur excavations there. H. Scheu and his son also used to send some Stragnai finds to Prussia Museum, but the greater part of the items were left as a part of a private collection in the Šilutė (Heydekrug) manor, where H. Scheu arranged some sort of exibition for visitors. Obviously Scheu’s collection of Stragnai items inspired A. Bezzenberger himself to carry out excavations there in 1902. A. Bezzenberger brought his, 1902 Stragnai finds to the Prussia Museum, but unfortunately be did not publish this material. Only the publication of S. Bolin in 1926 bears some information about Stragna cemetery graves with Roman coins findings. After the Second World War when Šilutė/Heydekrug manor lost its owners the old collection faced the threat of plundering. The main part of Stragnai cemetery finds were transported to Vilnius and became a part of the archeological collection in the main historical museum which is now Lietuvos nacionalinis muziejus. Now more then 2600 items known as Stragnai cemetery from formely Scheu collection (numbers of inventorisation LNM AR 38:1-2610) are kept there. A few dozen Stragnai items somehow were left in Šilutė where they survived under the eye of a semi-official curator and since 1949 then became a part of newly established Šilutė museum. Nowedays the Stragnai finds in this museum bear the following inventarisation numbers Nr. – 977–997, 2655–2727). It is difficult to reconstruct what type of systematization the Scheus used to keep their archeological collections in order – the finds that reached Vilnius were wrapped in newspaper or paper sheets. The items bad no individual labels. There were only Roman and Arabic numbers written on the some of paper-wrappings. The first Arabic number (as, 1899, 1900, 1901) must be supposed to be the year when particuliar items were found or dug up. Possibilities to explain meaning of Roman numbering and letters or small Arabic numbers written by them, for example “1899 VII” or “1900. B. III” (see Annex) are more complex. It seems that these could not mean the number of a grave, since items are signed in this way whose chronology is obviously different. The usual dating of Stragna cemetery finds from the Scheu collection is, 1th–13th cent. AD, most of the items represent either Later-Roman-Iron-Age or Viking-period types. The main aim of this article is to bring to general archaeological attention some mostly unpublished material from Stragnai cemetery, namely belt-tongues and some buckles that are close to them chronologically; various mountings and fittings for belts or bridles; mounting-plates for bridles. These items were selected for analysis as belonging to the Late Roman Age (some of them to Early Migration Period) using various known issues of typology for finds from the so called European Barbaricum. Belts-tongues (Riemellzungen by German terminology) in the Stragnai cemetery collection are mostly bronze ones with ring-formed endings (type J II according to K. Raddatz) – inv. Nr. (AR 38:482, 1681, 1681a, 1725, 1726 – see Fig. 1:1, 2, 3, 5, 4). According to the works of R. Madyda-Legutko such forms of belt ornaments were taken by the western Balts from the neighbouring Wielbark culture area at the beginning of the Late Roman Age and became more popular in Phase C1b. Belts-tongues from Stragnai inv. Nr. AR 38:482, 1681, 1681a (form J II:3 according to J. Ilkjaer) have close analogies with similar sorts of ornamentation found in graves sites in the Suwalki-Augustów region (Poland), where they represent the southwestern group of culture of the Balts at that time. Such belt-tongues were among the other bronze and silver belt ornaments in the famous “prince’s grave” in Szwajcarija barrow 2, the dating of which was considered to belong to Phase C2, or more accurately – Phase C1b. The style of surface ornamention of Stragnai belt tongues from group J II also helps to date these metal works to around the middle of the 3th second half of the 3th cent. Another bronze belt tongue of Raddatz-Ilkjrer group J II:3 from what is now the coastal region of Lithuania was found in male Grave 40 of Lazdininkai cemetery (Kretinga District) along with two iron sprearheads, one iron scythe, small ceramic pot and a bronze belt-buckle. These finds are preserved in the Kaunas museum (Vytauto Didžiojo karo muziejus) and the belt tongue from Lazdininkai Grave 40 is preserved under inventorisation number 1809:24. The evolution of the form J II:3 that reflects common characteristics of the Late Roman Age style in the Lithuanian coastal area, as we can deduce from the example of a belt tongue from Šernai (Schernen) cemetery Grave 3 (see Fig. 1:8). This find is known from A. Bezzenberger’s 1892 publication. Instead of having a hole of the ring, the Šernai belt tongue has blue glass surrounded by an ornamented wire circle. This “barbaric filigrane” used in the jewellry of the Baits is very typical of the second part of the Roman Iron Age. The Stragnai Collection contains a belt mounting tongue known by accession number AR 38:1682 which has an ear-form flat part in its centre and ends in an openwork rhombus with an end edge which is somewhat rough. This could be where the artefact was broken (see fig. 2:1). Among the finds from the Stragnai grave site there is a fragment of what we guess was a similar tongue (AR 38:1679) which is comprised of “little ears” with small holes (see fig. 2:2). Stylistically closest to the Stragnai finds are the openwork tongues with a rhomboid element that come from the Bogaczewo culture area. Such tongues are known from the Machary. Mojtyny grave sites and the so-called Pisanski Collection (fig. 2:3, 4) created by the Western Baits which is typical of the early phase of the Late Roman Period. A similar “baroque” form is typical of tongues from Gotland which were described in the work of O. Almgren and B. Nerman as belonging to the V:l Period (fig. 2: 5–7). The form of Stragnai tongue AR 38:1682 is connected with the Bogaczewo tongues by the basic openwork rhombus motif and in the Gotland examples we can detect an “ear” motif similar to that of AR 38:1679, 1682. The Stragnai AR 38:1682 mounting probably comes from the same burial phase as the above described J II:3 form tongues from the Stragnai Collection. Another openwork decoration from Stragnai (AR 38:2642, see fig. 2:8) was discovered in 1985 in the male and horse grave No. 13, which is dated to no earlier than the second half of C1b. The protruding “ear” motif is found in finds from another West Lithuanian grave site, Šernai (formerly Schernen, Kreis Memel), grave 50, which is dated to the C1b–C2 Period. These are two non-openwork belt mounting tongues. The top and “ears” of these mountings, like that of the filigrane pendant from Stragnai 13, are decorated with notched spirals and blue glass eyes (fig. 2:9 These forms appear to have developed from the simpler mounting tongue-type found in the Stragnai Collection (AR 38:1682). Item AR 38:481 represents some version of Raddatz types O 12–13, 15–16 belt tongues. An appearance of these forms in Wielbark culture area is dated from Phase Clb nether less the Stragnai example should be later. The way of ornamentation the latter reflects style of Phase C3 or even Phase D. The belt tongue of similar massive shape from Szurpily barrow I (Suwalky region, Poland) according to R. Madyda-Legutko belongs to the end of the Late Roman Age (see Fig. 3:2). It is difficult to find a strick analogy for the shape of Stragnai belt tongue AR 38:1655 (see Fig. 3:3) which seems to be some mixture of Raddatz types 1 IV:l and 1 IV:4. The front surface of Stragnai tongue is plated with tin. Some resemblance of its form it is possible to recognise in the belt tongue from Hassleben Grave 14(2), which belongs to Phase C2, though these similarities do not allow to fit Stragnai artefact into the same period. There are possible from the group of belt buckles found in the Stragnai cemetery to pick out these which could be regarded as Late Roman Age or Early Migration Period artefacts. A bronze buckle AR 38:1625 (see Fig. 4:1) is close to types M-L AD 17–18, 20–23 according to R. Madyda-Legutko typology, which are dated to the early stage of Late Roman Age. We can see some similarities between the shape of Stragnai buckle AR 38:1625 and the one from above mentioned Szwajcaria Barrow 2 grave, that allows us to suggest that the Stragnai buckle and tongues 1 II:3 (AR 482, 1681, 1681a) belong to the one set of grave goods or to the chronologically close group of graves. An iron buckle AR 38:1008 and three bronze buckles AR 38:1617, 1618, 1841 + 1631 (see Fig. 4:2–5) represent various versions of Madyda-Legutko group H and should be dated to the Early Migration Period (phase D). The similarity of the stamped ornamentation draw an attention when we see together bronze belt buckle AR 38: 1618 and tongue AR 38:481. If the form of the buckle AR 38:1841 + 1631 itself allows us to compare this buckle with the shape of some similar items ornamented in Untersiebenbrunn or Sösdala styles, the ornament of Stragna buckle shows juwellery technology of Balts. The same so called “fishscales” facetting is typical of classical Samland crossbow brooches with star-like feet (type II according to A. Bitner-Wróblewska), which are indicators of phase D, but continue to be in use in the beginning of phase E. Bronze fitting-detail with loop AR 38:697 (see Fig. 5:1) can be regarded as Zügelhake type 7B for bridle according M. Ørsnes classification. The elements for fitting leather bridle details of this type are known from another cemetery of the West Lithuania region – Adl. Heydekrug (Šilutė). Grave-goods from Adl. Heydekrug emerged as a result of amateur excavations of 19th cent., and full set of bridle details is known today on the ground of H. Jankuhn archive data. Similar briddle fitting-details were found in the grave sites of Bogaczewo culture and of its subregional group in Suwalki (Poland). However, fitting-details with loop could be also included into the set of metal fittings for a belt, but more likely such details as AR 38:697 and AR 38:1637 (see Fig. 5:3) had a function as joiners in bridle construction or harness strap-distributors. This hypothesis can be supported by another items of Stragnai which were part of horse bridle ornaments – lunula-shape pendants for forehead of horse inv. number AR 38:1705, 1707 (see Fig. 5:2, 4) and fitting-plates for bridle strap cross-sections inv. number AR 38:484, 485, 485a, 478, 479, 1650 (see Fig. 6:1–6). If we would try to establish some common features on the ground above described loose finds from Stragnai cemetery we will find that it bears many common characteristics with horse bridle constructions known from grave in Adl. Heydekrug (Šilutė), Maudžiorai Grave 1 (Kelmė district, Lithuania) or Altholillslerburg Grave 135 (now Chernakhovsk, Kaliningradskaia oblast’). This allows all above discussed fitting-details and ornaments for bridle to date in the time of 3th cent. AD. The fitting-detail with a “hook” AR 38:698 (see Fig. 7:1) at first sight seems to be a some kind of half-broken fitting with a slightly bent end, but the items of very similar shape found as an element of the horse bridle from the Szwajcaria borrow 2 “prince’s grave” (see Fig. 7:2) and Netta Grave 79 (both in Poland) help us to identify the function of the Stragnai loose find AR 38:698. This kind of fitting-detail was used for the joining of bridle-straps on a vertex of horse (see Fig. 7:3). Very similar fitting detail was also found in Rūdaičiai II horse’s grave 1 (Kretinga District, Lithuania). The chronology of above mentioned graves is established as phase C1b–C2, so it is possible to suppose that the fitting-detail with “hook” AR 38:698 came from Stragnai grave of approximately the same time. Analogies from the archeology of the North European Barbaricum help to establish the use of two oblongish fittings, whose corpus are bent – inv. numbers AR 38:483, AR 38:1663 (see Fig. 8:1, 2). The bent end of AR 38:1663 is partly broken, though the fitting-detail AR 38:483 represents the whole of its shape, which seems very similar to that of Riemenzungen known from the sets of belts of Late Roman Age found in Scandinavian votive sites (Ejsbøl I, Skedemose I). The iron fitting of similar form is known from the West-Balts territory in Netta cemetery grave 30 (male + horse burial) (see Fig. 8:3). The later was dated to 4th cent. AD. Often the surface of bronze ornaments of Late Roman Iron Age in West Lithuania region were tinned. That feature links four round bronze plates with two oblongish loops on the down sides AR 38:586, 1836, 1837; AR 38: without number (see Fig. 9:1–4) and round fitting plates – bridle’s distributors AR 38:478, 479, 1650 (Fig. 6:4–6). Could the oblongish loops be used to fit the plates freely on a leatheror textil-strap? The ways of fitting of Sarmatic phalerae (see fig. 9:5) suggest some possibilities of use such plates as AR 38:586, 1836, 1837; AR 38: without number in the equipment of horse. The third small loop which was fitted to plates AR 38:586, 1836; AR 38: without number could be used for keeping some pendant as illustrates provincial roman horse’s equipment from Zugmantel castle (see publication of Schleimacher) or horse’s bridle set from Žviliai Grave 47 (West Lithuania). The above-described loose finds of Roman Iron Age from formely Stragnai cemetery collection bear witness to the closeness of way of living of West Lithuanian region’s inhabitants of this time to that of other tribes of so-called Gennania Libera. As we see the archaeological material of one cemetery, though damaged to a considerably degree because of dramatic historical events of the middle of 20th cent., still remains valuable source.